Studying Juvenile Idiopathic Arthritis through a Network Medicine Approach - Prada-Medina, Cesar Augusto (2019)
Juvenile Idiopathic Arthritis (JIA) is a group of inflammatory conditions of unknown etiology whose underlying molecular pathophysiology is still not well characterized. Several studies have attempted to fill this gap by characterizing the gene expression profiles of JIA patients. However, there is a lack of systematic assessment of the reliability of these transcriptome results on the disease classification, prescription, and monitoring. In addition, despite this disease is more common in females, none of these studies have tried to assess the impact of sex on disease pathophysiology. In this project, we performed a comprehensive systematic review and a gene expression meta-analysis to reveal the core molecular JIA pathophysiology taking into consideration the patient sex. We gathered and cataloged more than 60,000 entries of genomic features reported as JIA-related in the functional genomics literature, and found a dramatic disparity among the JIA transcriptome studies. Near 15,000 genes have been reported as perturbed in JIA leukocytes. Less than one percent of these genes were reported in at least a quarter of the reviewed studies. We then removed the study-specific analytical bias by re-analyzing more than 700 unique pediatric transcriptome profiles from nine JIA studies using a common analytical framework. The differential expression results from different studies were combined using a random effect model meta-analysis approach. We implemented this differential gene expression meta-analysis methodology in the MetaVolcanoR R package that we made available in Bioconductor. Using this package, we confirmed several gene expression signatures previously associated with JIA and uncover new genes whose expression was perturbed in JIA patients. The effect sizes of the topmost reported perturbed genes coincide with our meta-analysis results. Through a meta-coexpression approach, we characterized the cell type signatures of circulating leukocytes in the JIA affected children. Additionally, we characterized the JIA sexual dimorphism. We found that systemic JIA female patients over-activate a gene expression signature which comprises early myelocytes and band neutrophil expression markers. This signature is correlated with the disease status and response to IL-1 receptor blockade. This suggests that sJIA pathophysiology is characterized by a sexually dimorphic neutrophilia that impacts disease progression and the response to anti-IL-1 treatments. We further assessed this immature neutrophil and female-biased signature in other contexts. We found that this signature presents a sex-dependent expression over human lifetime, in other inflammatory diseases, and its expression increases during pregnancy.